Association Between Western-Style Dietary Exposures and Hypertension Among Adults: A Systematic Review - Nurfatmi, Rezki; Sochibahariani, Putri Demylia (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Introduction: Hypertension is a major global public health issue, affecting over 1.28 billion adults worldwide, with increasing prevalence in both developed and developing countries. Western dietary patterns, characterized by high consumption of processed meats, ultra-processed foods, sugary beverages, and high-sodium items, alongside low intake of fruits, vegetables, and whole grains, have been linked to elevated blood pressure and cardiovascular risk. This systematic review sumkimzes the evidence on the association between Western food consumption (including ultra-processed and fast foods) and hypertension in adults, and discusses its implications for public health and future research. Methods: Following PRISMA 2020 guidelines, a literature search was conducted in PubMed, Scopus, and ScienceDirect using keywords such as